1997
DOI: 10.1007/s001340050453
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of prone position in critically ill patients with acute respiratory distress syndrome

Abstract: Turning critically ill, severely hypoxemic patients from the supine to the prone position is a safe and useful therapeutic intervention. Our data suggest that prone positioning should be carried out early in the course of ARDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
95
0
7

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(109 citation statements)
references
References 31 publications
6
95
0
7
Order By: Relevance
“…Prone positioning, reported for the first time in 1976 by Piehl et al [79] has a special place in lung recruitment. Most studies found an improvement in oxygenation, although a substantial number of patients do not respond and the beneficial effect usually disappears after reversal to the supine position [60,70,71,[80][81][82][83][83][84][85][86]. The increase in oxygenation in the prone position is explained by recruitment-related mechanisms such as improved ventilation through decreased alveolar compression by the heart and recruitment-independent mechanisms, e.g.…”
Section: Human Studiesmentioning
confidence: 99%
“…Prone positioning, reported for the first time in 1976 by Piehl et al [79] has a special place in lung recruitment. Most studies found an improvement in oxygenation, although a substantial number of patients do not respond and the beneficial effect usually disappears after reversal to the supine position [60,70,71,[80][81][82][83][83][84][85][86]. The increase in oxygenation in the prone position is explained by recruitment-related mechanisms such as improved ventilation through decreased alveolar compression by the heart and recruitment-independent mechanisms, e.g.…”
Section: Human Studiesmentioning
confidence: 99%
“…10 Moreover, patients with chronic heart failure because of CAD prefer the right lateral decubitus position for significantly longer periods of time than either the left lateral decubitus or supine position, because the sympathetic nervous modulation is most attenuated in this position. 11,12 Modern medical research has found that the prone position can improve the arterial oxygen tension in acute lung injury (ALI) and acute respiratory distress syndrome (ARDS), [13][14][15][16][17][18] and is one of the suitable positions used during general or spinal anesthesia. 19,20 ALI and ARDS are severe clinical conditions that are associated with severe oxygenation failure and very high mortality rate.…”
mentioning
confidence: 99%
“…Com relação aos parâmetros ventilatórios utilizados nos três momentos da pesquisa (Pinsp, f, FiO 2 , Vt, e Ve), não foram observadas modificações significativas em nenhuma das fases propostas. Porém, ao relacioná-los isoladamente notou-se que: quanto maior o valor da PEEP e menor volume-corrente, complacência estáti-ca, pH, PaO 2 , e SaO 2 maior a mortalidade 15,22,34,[35][36][37][38][39][40][41][42][43][44] . Optou-se em realizar o protocolo iniciando na posição supina, pela facilidade de todos os pacientes estarem nesta posição, no entanto se tivessem sido aleatorizados e alguns iniciassem o estudo na posição prona, talvez os resultados pudessem ser diferentes do exposto pela diminuição do efeito carry-over ou de evolução temporal da doença.…”
Section: Discussionunclassified